Optical coherent dot-product chip for sophisticated deep learning regression - Shaofu Xu (Nature Publishing Group, 2021)
An optical coherent chip completes state-of-the-art image reconstruction tasks with 32-bit computer comparable image quality, showing potential in conquering sophisticated deep learning regression tasks.